Material deprivation and unemployment affect coercive sex among young people in the urban slums of Blantyre, Malawi: A multi-level approach. (May 2015) - Kamndaya, Mphatso; Kazembe, Lawrence N.; Vearey, Jo; Kabiru, Caroline W.; Thomas, Liz
Abstract: We explore relations among material deprivation (measured by insufficient housing, food insecurity and poor healthcare access), socio-economic status (employment, income and education) and coercive sex. A binary logistic multi-level model is used in the estimation of data from a survey of 1071 young people aged 18–23 years, undertaken between June and July 2013, in the urban slums of Blantyre, Malawi. For young men, unemployment was associated with coercive sex (odds ratio [OR]=1.77, 95% confidence interval [CI]: 1.09–3.21) while material deprivation (OR=1.34, 95% CI: 0.75–2.39) was not. Young women in materially deprived households were more likely to report coercive sex (OR=1.37, 95% CI: 1.07–2.22) than in non-materially deprived households. Analysis of local indicators of deprivation is critical to inform the development of effective strategies to reduce coercive sex in urban slums in Malawi. Highlights: Local measures were used for an analysis of association between deprivation and coercive sex. Unemployment was associated with coercive sex among young men. Material deprivation was associated with coercive sex among young women.